Intergrating STEAM Education in Organization of Activities for Children to be Confidental with Literature Works in Kindly School - Tu, Van Thi Minh; Nhung, Chu Thi Hong; Huong, Nguyen Thu (VNU Journal of Science: Education Research, 2022)
Literature has great significance in early childhood education. Introducing children to literary works plays an important role in the preschool education program. Integrating STEAM education in preschool activities in teaching literary works is considered an effective method of educational improvement, in line with the innovation requirements in teaching specific subjects. This teaching approach brings many practical values not only for learners but also for teachers. Through studying the theoretical and practical basis of STEAM education in preschool education, the article explains the suitability of integrating STEAM education in teaching literary works, thereby proposing a practical process. The current paper proposes the integration of STEAM education in organizing activities to familiarize children with literary works in preschool.